P1260INTRA CRANIAL AND HEART VALVES CALCIFICATIONS IN HEMODIALYSIS PATIENTS - INTERRELATIONSHIP AND CLINICAL IMPACTS. (6th June 2020) - COHEN HAGAI, KEREN; Fanadka, Feda; Grumberg, Tania; Topaz, Guy; Nacasch, Naomi; Greenberg, Meidad; Zitman-Gal, Tali; Benchetrit, Sydney
Abstract: Background and Aims: Arterial calcification is an integral component of active atherosclerosis and is an independent risk factor for cardiovascular disease. Intra-cranial calcification (ICC) in hemodialysis (HD) patients has a prevalence of about 90%, and its severity is correlated with age, hemodialysis vintage and mineral bone disease. Heart valves calcifications are also considered as a local manifestation of atherosclerosis and have been associated with poor cardiovascular outcomes. This study assessed the correlation between valvular and ICCs in hemodialysis patients and its clinical impact on mortality. Method: A blinded neuroradiologist graded ICC of all HD patients who underwent non-contrast brain computerized tomography (CT) from 2015 to 2017 in our institution. Valvular calcifications were recorded according to echocardiography study. Only hemodialysis patients with available echocardiography and brain CT were included. Results: This retrospective study included 119 hemodialysis patients (mean age 70.6±12.6 years, 57.1% male). Of the total cohort, 19 (16%) had no cardiac or brain calcifications and 65 (54.6%) had both valvular and intracranial calcifications. Considering the patients with no calcification as the reference group yielded adjusted odds ratios for all-cause mortality of 3.68 (95%CI 1.55-8.75) among patients with any brain calcifications, p=0.002. ICC was the most important predictor of mortality in the study cohort. Conclusion: We found an independent association between ICC and the risk of death among hemodialysis patients. Assessing ICC in non-contrast CT may contribute to the risk stratification of HD patients. These calcifications are no less important than valvular calcifications are. Additional studies are needed to confirm these findings.